Analysis of the Fountain Solution in the Offset Printing in Terms of Printability - Cem Özakhun, Sükrü; Bünyamin Zelzele, Ömer; Özcan, Arif (Asian Journal of Chemistry, 2011)
Fountain solutions have been used in the offset lithographic printing for decades. They are water-based solutions applied immediately before or after the ink is applied to the printing plates. Today, fountain solutions are used all around the world and the experienced printers constantly struggle with the issues of the compatibility of the fountain solution with the ink and the alcohol or acid replacement. The most ideal way is to have a fountain that is neutral, effective and completely compatible with all inks.